2019
DOI: 10.2147/cmar.s218179
|View full text |Cite
|
Sign up to set email alerts
|

<p>Magnesemia: an independent risk factor of hypocalcemia after thyroidectomy</p>

Abstract: Background This study was designed to investigate the impact of serum magnesium (Mg) levels on hypocalcemia after thyroidectomy. Patients and methods In total, 242 patients with differentiated thyroid cancer were retrospectively analyzed. Results Multivariate regression analysis showed hypomagnesemia was an independent risk factor for hypocalcemia ( P <0.001). While Mg in low levels (0.66 mmol/L ≤ Po-Mg ≤0.74 mmol/L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 29 publications
2
24
0
3
Order By: Relevance
“…Hypocalcemia often occurs after hypoparathyroidism. Some scholars have reported that the magnesium concentration after thyroid surgery is closely related to hypoparathyroidism [25][26][27][28]. We also nd that Pod7 Mg and Pod7 P are effective predictors of the return of PTH to normal levels on Pod7.…”
Section: Resultssupporting
confidence: 51%
“…Hypocalcemia often occurs after hypoparathyroidism. Some scholars have reported that the magnesium concentration after thyroid surgery is closely related to hypoparathyroidism [25][26][27][28]. We also nd that Pod7 Mg and Pod7 P are effective predictors of the return of PTH to normal levels on Pod7.…”
Section: Resultssupporting
confidence: 51%
“…3,9,10,[15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34] The quality of all included studies was assessed using the NOS, of which 10 studies were rated as high quality (four with 8 stars and six with 7 stars) and 13 studies were rated as moderate quality (11 with 6 stars and two with 5 stars) (Table 1). 3,9,10,[15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34] According to the heterogeneity for the meta-analyses on preoperative vitamin D levels (I 2 ¼ 74%, P ¼ 0.010), preoperative PTH (I 2 ¼ 92%, P < 0.0001) and preoperative calcium levels (I 2 ¼ 79%, P < 0.0009), a random-effects model was used for the meta-analyses. According to the heterogeneity for the meta-...…”
Section: Resultsmentioning
confidence: 99%
“…Some authors emphasize the importance of postoperative measurement of PTH and the fact that a decrease in their levels can predict the development of hypocalcemia due to thyroidectomy (19). When symptoms occur after thyroidectomy, both calcium and magnesium should be corrected and monitored (20). Thus, the measurement of calcium, magnesium, PTH and thyroid hormones is proposed in patients with risk factors who will undergo surgery.…”
Section: Discussionmentioning
confidence: 99%